2013
DOI: 10.1111/1911-3846.12001
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Enterprise Systems Implementation on the Firm Information Environment

Abstract: This study uses an archival research design to assess the impact of enterprise systems on a firm's internal information environment as reflected in the production of management earnings forecasts. Specifically, the authors hypothesize that, if enterprise systems improve management's access to decision‐relevant internal information, higher quality management earnings forecasts should ensue. Consistent with disclosure theory and the purported technical characteristics of enterprise systems, the authors find a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(74 citation statements)
references
References 73 publications
(93 reference statements)
0
72
1
1
Order By: Relevance
“…Other studies find that investments in IT increase financial and market performance (e.g., Bharadwaj 2000; Zhu and Kraemer 2002) and improves organizational innovativeness (Kleis et al 2012;Xue et al 2012) across different contexts. Dorantes et al (2013) report that Enterprise Systems improve companies' internal information environment and increases both quantity and quality of management forecasts. Kobelsky et al (2008) suggest that investing IT is essentially a way for companies to realize their strategic goals of improving future performance.…”
Section: The Benefits Of Itmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies find that investments in IT increase financial and market performance (e.g., Bharadwaj 2000; Zhu and Kraemer 2002) and improves organizational innovativeness (Kleis et al 2012;Xue et al 2012) across different contexts. Dorantes et al (2013) report that Enterprise Systems improve companies' internal information environment and increases both quantity and quality of management forecasts. Kobelsky et al (2008) suggest that investing IT is essentially a way for companies to realize their strategic goals of improving future performance.…”
Section: The Benefits Of Itmentioning
confidence: 99%
“…Our research fills this gap by examining IT and audit risk in an integrated research setting. Second, prior accounting literature, such as Hayes et al (2001), Ranganathan and Brown (2006), and Dorantes et al (2013), documents the effects of IT by using an indicator variable to represent whether companies implement Enterprise Systems specifically (ERP, SCM, CRM system, etc.) or not.…”
Section: Introductionmentioning
confidence: 99%
“…ERP, according to the literature, can, it is argued, affect the forecasting quality (Dorantes et al 2013). Nevertheless, this research found that this statement is based on many assumptions.…”
Section: Erp Planning Benefitsmentioning
confidence: 99%
“…Especially financial and non-financial information and eliminating barriers between entity's value chains located within and across organization give managers opportunities to manage everything with real-time information (Dorantes, Li, Peters andRichardson, 2013: 1430). ERP is expected to automate formal MCS tasks and provide opportunities for informal-based MCS.…”
Section: Erp-mcs Relationshipmentioning
confidence: 99%